Small RNAs, Big Potential: The Role of MicroRNAs in Stem Cell Function - Foshay, Kara M.; Gallicano, G. I. (Current Stem Cell Research & Therapy, 2007)
MicroRNAs (miRNAs) are a newly discovered, yet powerful mechanism for regulating protein expression via mRNA translational inhibition. Loss of all miRNA function within mice leads to embryonic lethality with a loss of the stem cell population in the epiblast and failure to form a primitive streak. These data suggest that miRNAs play a major role in embryonic development. As critical regulation of protein expression is also important for controlling the balance between self-renewal and differentiation in stem cells, the study of miRNAs within this model system is rapidly expanding. New data suggest that stem cells have discrete miRNA expression profiles, which may account for, or contribute to, the intrinsic stem cell properties of self-renewal and pluripotency. Specifically, miRNAs have been implicated in downregulation of cell cycle checkpoint proteins during germ stem cell division. Other data demonstrate that changes in miRNA expression can promote or inhibit stem or progenitor cell differentiation within different cell lineages, including hematopoietic cells, cardiomyocytes, myoblasts, and neural cells. In this review we detail the established functional roles of miRNAs in the embryonic and adult stem cell model systems. Finally, we explore new techniques that exploit endogenous miRNA processing and function for applications in basic and clinical research.
Keywords: Cardiac Progenitors